2022
DOI: 10.3846/jcem.2022.16995
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Diverse Sizes of Coal Bottom Ash as Fine Aggregate in the Performance of Lightweight Foamed Concrete

Abstract: In recent years, research work on the use of coal bottom ash (CBA) as a partial alternative for aggregate in concrete is on the rise. This research is aimed at examining the characteristics of lightweight foamed concrete with CBA as fine aggregate to produce environmentally sustainable product. With the volume replacement technique, CBA was used as 25%, 50%, 75%, and 100% replacement for conventional mining sand with different sieve sizes of smaller than 4.75, 2.36, and 0.6 mm in concrete. Water absorption, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The water absorption rate was 3.8% without CS and increased to 4.2% when 10% CS was added. Strzalkowski et al [21] found that adding CS(0%) resulted in 2.5% water absorption, while adding CS(20%) increased it to 3.8%. Haddadian et al [22] used coal bottom ash and found that CBA(0%) had 12.96% water absorption, while CBA(25%) had 20.15%.…”
Section: Durability Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…The water absorption rate was 3.8% without CS and increased to 4.2% when 10% CS was added. Strzalkowski et al [21] found that adding CS(0%) resulted in 2.5% water absorption, while adding CS(20%) increased it to 3.8%. Haddadian et al [22] used coal bottom ash and found that CBA(0%) had 12.96% water absorption, while CBA(25%) had 20.15%.…”
Section: Durability Propertymentioning
confidence: 99%
“…Additionally, there was a loss of mass, indicating the effects of high temperature on the structural integrity of concrete. Strzalkowski et al [21] explored the impact of cenosphere concentration on thermal conductivity. In the same study it was found that, as the concentration of cenospheres increased, the thermal conductivity of the concrete decreased.…”
Section: Thermal Propertymentioning
confidence: 99%